Geo-electric Laboratory Simulation for Characterization of Hydrocarbon Impacted Coastal Sands - S. Sualla; M. N. Tijani; M. A. Oladunjoye; O. A. Oki (Archives of Current Research International, 2018)
An electrical resistivity experiment was undertaken using a laboratory model tank with the aim of simulating and characterizing hydrocarbon spills on coastal sands. Prior to injection of fluids, geo-electric measurements were done as a control, subsequently injection of crude oil into the model tank was undertaken and geo-electric measurements carried out. Seven (7) electrical traverse lines were established in the tank and measurements were taken for two (2) scenarios of baseline environment and hydrocarbon impacted environment making a total of fourteen (14) geo-electric profiles. Measurements were made using dipole-dipole array, and inversion using DIPRO software to obtain the 2-D geo-electrical models. Textual and hydraulic characterization showed the medium was well sorted fine to medium grain sand. Pre-injection inverted data obtained for all the traverses revealed that the porous medium exhibited heterogeneity which was more evident on traverse 5, 6 and 7 compared to traverse 1, 2, 3, and 4. Images obtained showed high resistive anomaly reflected the presence of crude oil plume within the coastal sand. Resistivity profiles along the main lines showed migration of the hydrocarbon plume was more prominent along traverse 6 and 7, due to high hydraulic conductivity sands. Also, in comparison to the orthogonal lines, traverses 1, 2, 3 and 4 clearly delineated hydrocarbon plumes. Results from this study demonstrated a successful application geo-electric investigation for characterization of hydrocarbon spills in the soil, which would aid efficient remediation designs.